Land tenure and social relations in matrilineal and uxorilocal societies in Malawi - Daimon Kambewa; Erling Berge; Stanley Khaila; Alister C. Munthali; Henrik Wiig (Norwegian University of Life Sciences (NMBU), Centre for Land Tenure Studies (CLTS), 2023)
This paper is about social relations in customary lands for the matrilineal uxorilocal culture of the Lomwe, Nyanja and Yao tribes in Southern Malawi. The study was carried out in the districts of Chiradzulu and Phalombe. Qualitative methods were used to examine local histories and practices to identify the social and power relations between males and females in matrilineal groups and the roles of chiefs, extended families, and traditional practices in access to and control over customary land. By focusing on local histories the study documents that patterns of access to and control over customary lands are historical in nature and embedded in social ties and power relations. Male and female members of the household or family have equal use rights but unequal ownership rights. The land belongs to the extended family and not to the community or individuals. Instead of saying the land belongs to 'me' the people say the land belongs to 'us' even though the individuals may have user rights in perpetuity. The 'us' implies the extended family and not the community. The power and control over the land is located in the group of sisters and not in the head of family (mwini-mbumba) or the Chief. The patterns of control have to be understood for proper decisions to be made on how to organize access to and control over land, especially in a country where livelihoods are dependent on agriculture or are land based in nature.
Keywords: Q15; P14; P26; P48; D23; 330; matrilineal; matrilocal; uxorilocal; land tenure; access rights; use rights; ownership rights; Yao; Lomwe; Nyanja; Malawi